Model Pengembangan Lembaga Penyiaran Publik Lokal (LPPL) Radio di Jawa Tengah - Wiratmo, Liliek Budiastuti; Irfan, Noor; Samudi, Samudi (Universitas Semarang, 2016)
Local Public Broadcasting radio is broadcasting reform that seeks to restore the sovereignty of the people as the owners of the frequencies through Act No. 32 of 2002 on Broadcasting. Government Regulation No. 11/2005 create the space to Local Government Radio Broadcasting can adjust to the regulations on LPPL Radio. However, up to ten years since the birth of the Broadcasting Act, the presence of LPPL Radio presence in Central Java has not been fully able to show a real role. This study used a qualitative approach through bencmarking studies between LPPL radio with the Broadcasting Licence and the Broadcasting Operation Principle Permit, which is Radio Swara Kendal FM; Radio Kota Batik, Pekalongan; Radio Singosari, Brebes; In FM Radio, Kebumen; Irama FM Radio, Purworejo and LPP RRI Semarang. The result of this research is the Local Public Broadcasting Radio development model accordance with applicable regulations.